Secrets of the trading pros : - Bouroudjian, H. Jack (John Wiley & Sons, 2007)
Now, with Secrets of the Trading Pros, Bouroudjian shares this carefully guarded information with you, and reveals how it can be used to enhance your daily trading endeavors. Through engaging stories and illustrative examples, Bouroudjian sheds much needed light on the dynamics that drive the market from day to day, and discusses how you can capitalize on the price action created from its volatility. And while a majority of the book focuses on the importance of fundamental information, and how new developments are factored into prices, Secrets of the Trading Pros also looks at the predictable behavior of market participants and explains how you can benefit from these situations as well.